Battling for the Bible: Academy, Church and the Gay Agenda. Issue 15 (15th January 2013) - Guest, P.
Abstract : This paper considers the fact that the academic resources of contemporary biblical scholarship are employed by both sides in the Church debate on homosexuality. When historical and critical evidence has been marshalled, decisions continue to be made on the basis of prior commitments to deeply held theological convictions. This being the case it is important to consider the role that biblical scholars play in debate. It can no longer be considered adequate that they continue to supply supposedly objective knowledge concerning the texts while remaining silent concerning the ethics of interpretation. In the future queer theology will exercise a profound impact and queer readings that move beyond the current boundaries of 'legitimate' interpretations will proliferate. This will radically reshape the terrain on which debate takes place. However, at the present moment, there is an urgent need to question the ethics of interpretation within the academy itself.